Effects of great bustard (Otis tarda) gut passage on black nightshade (Solanumnigrum) seed germination. Issue 3 (September 2014) - Bravo, C.; Velilla, S.; Bautista, L.M.; Peco, B.
Abstract Birds are important seed dispersers for fleshy fruits through their transportation of ingested seeds. The seeds of many species germinate faster and in greater proportions after passing through a digestive tract, although the effects of this passage vary amongst bird and plant species. Many factors determine the germination success of ingested seeds, such as seed scarification during the digestion process, the fertilizing effect of droppings and the removal of pulp surrounding the seeds. In central Spain, the great bustard (Otis tarda) may act as a disperser of European black nightshade (Solanum nigrum). We analysed the germination success of ingested and non-ingested S. nigrum seeds. The fertilizing effect of bustard droppings and the disinhibition effect of the removal of Solanum pulp on final germination percentage, germination speed and viability were also assessed. Although ingested seeds germinated faster than non-ingested seeds, the former showed a lower germination percentage than the latter: 80–87% versus 99%. Droppings and fruit pulp showed no effect on germination enhancement, except in one aspect: the germination speed of non-ingested seeds decreased when they were sprayed with a fruit extract. We confirm that seeds ingested by great bustards had lower germination success than non-ingested seeds. Although seed ingestion by great bustards reduced seedling emergence, the number of emerged seedlings was still quite large. Thus, great bustards may play a role as a S. nigrum seed dispersal vector.